The Comparison and Test of Antioxidant Activity of Ethanol Extracts of Pangi Leaves and Seeds (Pangium Edule Reinw.) Using the DPPH (1,1-Diphenyl-2-Picrylhydrazyl) Method - Suleman, Abdul Wahid; Sari, Nurmala; Safaruddin, Safaruddin; Adri, Tenri Ayu; Siradjuddin, Mutmainnah; Prihandari, Ayu (Universitas Muhammadiyah Klaten, 2024)
The leaves and seeds of pangi (Pangium edule Reinw.) contain alkaloids, flavonoids, saponins, and tannins, which acts as antioxidants. Antioxidants are needed to protect the body and inhibit the negative impact of free radicals due to the oxidation reactions that occur. Antioxidants are compounds that inhibit oxidation reactions by binding free radicals and molecules. This research aims to determine the comparison of the antioxidants activity of pangi (Pangium edule Reinw.) leaves and seeds using the DPPH (1,1,-Diphenyl-2-Picrylhydrazyl) method. Reactive research method, experimentally, namely by carrying out serial dilutions of concentrations of 10, 20, 30, 40 and 50 ppm in each test solution, then adding the DPPH solution and measuring the antioxidants activity with a UV-Vis Spectrophotometer. After that, the IC50 (Inhibitor Concentration 50) value and the AAI (Antioxidant Activity Index) value are calculated, and the data were analyzed using ANOVA. The results of calculating the IC50 and AAI values are that the IC50 value of the pangi leaf ethanol extract is 49.6061 ppm (AAI=1.007), while the IC50 value of ethanol extract of pangi seeds is 50.2027 (AAI=0.9959). From the results of research and data analysis, it can be concluded that the ethanol extract of pangi leaves has higher antioxidant activity compared to the ethanol extract of pangi seeds.